Pentahelix Stakeholder Synergy in SMEs Development to Accelerate the Achievement of Village SDGs Targets - Rahmawati, Teti; Enung Nurhayati; Herma Wiharno; Andri Ahyanto; Rencha Nur Marsandi (IMPACTS: International Journal of Empowerment and Community Services, 2024)
Purpose This community service aims to to achieve the Penta helix synergy of stakeholders who can be involved in MSME development to accelerate the achievement of Village SDGS targets. Methods - The method that will be used in this activity is the Participatory Development approach which involves community participation in the implementation of activities Result and discussions - The pentahelix concept combines their roles to develop knowledge innovation. These different potentials can be transformed into products and services that are valuable and beneficial to society. Through this Service Activity, FGD has been carried out among stakeholders consisting of MSME Players, Industry Players who will accompany MSMEs, Village Government, Community, LPM, Media, and Academics. In the FGD, their respective roles and duties were outlined to assist the development of MSMEs in the Ciporang sub-district. stakeholders consider that MSMEs have a reasonably high contribution in achieving the Village SDGS target. The average perception of all stakeholders is above 70 percent. Even for village governments, it is considered that MSMEs contribute to achieving SDGS targets above 80%. Conclusion - Five community elements are involved in the pentahelix collaboration for MSME development to support the acceleration of SDGS achievement: Academy, All stakeholders consider that MSMEs contribute reasonably well to achieving the Village SDGS target. The average perception of all stakeholders is above 70 percent. Even for village governments, it is considered that MSMEs contribute to achieving SDGS targets above 80%.